ANALYSIS OF CHALLENGES AND OPPORTUNITIES IN THE DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE DIGITAL ERA: FUTURE PERSPECTIVE - Br.Sinulingga, Sadepa Putri; Nasution, Muhammad Irwan Padli (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Abstrak. Technology has become an integral part of human life, aiming to enhance efficiency and effectiveness. Modern businesses also operate within a digital environment that connects individuals and organizations. The digital world is a global phenomenon, fully driven and supported by new technologies. Digitally and fundamentally, the millennial generation must be able to utilize digital technology, have the tools and infrastructure to leverage it, and effectively use social media as a marketing tool for their companies.The approach taken in composing this article involves carefully gathering information from reputable national publications and employing a qualitative research approach. The purpose of this analysis is to identify the challenges and opportunities arising from the rapid innovation in ICT and to explore how future developments are likely to shape global society. The main challenges include the significant digital divide between developed and developing regions, concerns over data security and privacy, and the need to strengthen the workforce’s readiness for digital transformation.On the other hand, ICT advancements present substantial opportunities for the future. Technologies like artificial intelligence (AI), the Internet of Things (IoT), and blockchain enable the creation of new innovations, accelerate digital transformation processes, and enhance operational efficiency across various industries. Moreover, these technologies have great potential to support the growth of the digital economy, create new job opportunities, and improve people’s quality of life.